PENGARUH FAKTOR BUDAYA, SOSIAL, PRIBADI DAN PSIKOLOGI TERHADAP KEPUTUSAN MEMBELI DI INDOMARET ( Studi Kasus Pada Mahasiswa Fakultas Ekonomi Universitas Katolik Santo Thomas Sumatera Utara ) - Tamba, Darwis (UNIKA Santo Thomas, 2017)
The aim of this research, analyze the influence of cultural, social, personal and psychology of the buying decisions in Indomaret and analyzes of the four variables: cultural, social, personal and psychological variables which are the most dominant influence on buying decisions in Indomaret. Benefits study provides empirical evidence about the influence of cultural, social, personal and psychological on purchase decisions in Indomaret, provide knowledge to the public about cultural, social, personal and psychology of the buying decisions in Indomaret and contribute to the academic community about the importance of knowing the effect of factors cultural, social, personal and psychological on purchase decisions. The study population across the Faculty of Economics of the Catholic University of Santo Thomas North Sumatra ever shopped at Indomaret district of Medan Selayang while the study sample sebahagian the population can be considered representative. The total sample of 100 respondents, the type of data used primary and secondary data and data collection tools through questioner and documentation. Data analysis tool used regression. The results showed the multiple linear regression equation: KM = 3.503 + 0,122FBu 0,016FSo + + + 0,337FPsi 0,246FPri. The equation shows that cultural factors, social factors, individual factors, and psychological factors have a positive influence on the purchase decision will be positive. By F test, showing that the test results simultaneously (Test F) note the value F = 15.672 significance of 0.000